The halo effect of biofortification claims on taste inference and purchase intention - Chen, Tong; Gabrielyan, Gnel; Shimizu, Mitsuru; Qing, Ping (British food journal (1966), 2021)
PurposeThe purpose of this research is to investigate how biofortification claims impact consumer food taste inference and purchase intention. Based on the halo effect, the authors propose that food products with biofortification claims are inferred to taste better than regular foods. Due to this inference, biofortification claims subsequently improve purchase intention.Design/methodology/approachTo examine these predictions, the authors conducted three between-subject design lab experiments featuring three staple foods: corn soup (β-carotene biofortification claim present or not), cooked rice (zinc biofortification claim present or not) and uncooked rice (zinc biofortification claim present or not). Participants were randomly assigned to one of two bioproduction claim conditions (present vs absent). Then, taste inference, purchase intention, consumer characteristics and confounding variables were measured.FindingsIn Experiment 1, the results showed that biofortification claims indeed appeared to evoke a heuristic halo effect, in which foods with biofortification claims were inferred to taste better than regular food. In Experiment 2, the results showed that participants had more intention to purchase foods with biofortification claims than regular food. The mediation effect of taste inference between biofortification claims and purchase intention was examined. In Experiment 3, the data further showed that this halo effect was more pronounced when consumers held a higher preference (vs lower preference) for the enriched nutritional element.Originality/valueBiofortification claims have commonly been viewed solely as information about nutrition value for consumers. However, little is known about how biofortification claims impact hedonic consumer expectations. In this paper, the authors find that biofortification claims alone can impact consumer food taste inference, as nutritional information is not related to actual food taste. These findings extend the authors’ understanding of the psychological mechanism behind consumer attitudes towards biofortification.